Histopathological Spectrum of Hysterectomy Specimen in Sonographically Bulky Uterus among Peri and Post-Menopausal Women: Histopathology of Bulky Uterus - Khurram, Nosheen; Maryam, Attka; Raza, Almas; Mahmood, Anam; Afzal, Madiha; Aziz, Uzma (Pakistan Journal of Health Sciences, 2025)
A common sonographic characteristic in peri- and postmenopausal women is a sonographically bulky uterus, often associated with diverse uterine abnormalities, necessitating histopathological evaluation. Objective: To assess the histopathological changes in hysterectomy samples of peri- and post-menopausal females with sonographically enlarged uterus. Methods: The study participants were 150 postmenopausal women with a bulky uterus by ultrasound. This study was cross sectional and carried out in the Obstetrics and Gynaecology Department of Rashid Latif Meical College, Lahore from February 2022 to January 2024. Histopathological assessment was done on hysterectomy specimens to compare various diseases of the uterus including fibroids, endometrial hyperplasia, endometrial cancer, adenomyosis, and other benign/malignant diseases. Data were analyzed using SPSS version 23.0 and descriptive and comparative analysis methods including chi-square, Fisher exact test and logistic regression. Results: The majority of the participants, 53.33 % were peri-menopausal while 46.67 % were post-menopausal. The symptomatic complaints were abnormal bleeding and pelvic pain with rates of 60% and 33.3%, respectively. Uterine size greater than 12 cm was found to be more common in peri-menopausal women 62.5% compared to post-menopausal women 42.86%; p=0.02. Histopathology assessment showed that endometrial hyperplasia 37.5% vs 14.29%, p=0.02 and fibroid 50% vs 28.57%, p=0.02 were higher in peri-menopausal women. There were no statistically significant differences between the two groups for endometrial carcinoma, adenomyosis, cervicitis or atrophic endometrium. Conclusion: The women in their peri-menopausal period that had sonographically enlarged uteri had a higher rate of fibroids and endometrial hyperplasia than the post-menopausal women.